A Participação Digital em Atividades Culturais - Caso de Estudo: Comissariado Cultural da FEUP - Raquel Pinto de Magalhães Correia (2017)
In the current context, Digital Participation, a process characterised by the creation, development and dissemination of ideas by people through digital tools, assumes an increasingly significant role in the communication strategies used by Higher Education Institutions (HEIs) at national and international level. The Cultural Commissariat was created in 2002, with the main objective of organising regular cultural programmes which promote participation and artistic appreciation for those connected to the Faculty of Engineering of the University of Porto (FEUP). Curated cultural activities range from music to performing arts, through debates on art and society, to exhibitions and film screenings. The need to make an effective diagnosis, with the intention of frequently updating the strategies of digital communication, is the objective of this project, attending that the dissemination of cultural activities must be adapted to the target audience. The validity of the present research is verified through results obtained in Focus Group sessions and online questionnaires. The purpose is to energise a set of digital communication channels adapted to aspects of the surrounding community. Based on a bibliographical review, which focuses on Strategic Marketing, more specifically on HEIs, this work suggests a digital communication strategy that meets the objectives outlined.